MENCARI BENTUK REKONSILIASI INTRA-AGAMA: Analisis terhadap Pengungsi Syiah Sampang dan Ahmadiyah Mataram - Cahyo Pamungkas (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2018)
This article aims to answer a three of questions as follows: first, whether reconciliation between the refugees of Islam minorities, Shia Sampang andAhmadiyah Lombok, and Sunni’s majority in their hometown still possible? Second, if it is still possible how to implement it and what constraints do arise? Third, theoretically, which model of reconciliation is in accordance with the context of the intra-religious conflict in Indonesia? This article is written based on the study of literature and field research, conducted by LIPI research team, which seeks to identify conditions or necessary conditions to achieve reconciliation between displaced Islamic minority and Islamic majority live in their places of origin. The issue of reconciliation is very important, considering both the refugee community is Indonesian citizens who have the right to be protected. However, in reality, they like to be in a quarantine so-called refugee camps. The proposition of this article is reconciliation among communities displaced by the public place of origin is possible with certain conditions such as the strong implementation of the fulfillment of human rights, cultural context and theological beliefs that support the peace process, and the role of active government in pushing the peace process.